Willy Brandt : the life of a statesman - Miard-Delacroix, Hélène (I.B. Tauris, 2019)
"He was at the forefront of some of Germany's most definitive and controversial decisions, in his role as the first Social Democrat Chancellor of West Germany between 1969 and 1974. In this period he paved the way for the eventual reunification of the country, as well as strengthening European integration in western Europe. In 1971, he received the Nobel Peace Prize for 'Ostpolitik', his policy of reconciliation with Germany's neighbours in the Eastern Bloc. During the treaty negotiations in Warsaw, he famously fell to his knees in recognition of the atrocities committed by his countrymen in the Warsaw Ghetto. This definitive new biography illuminates Brandt's personal life and political career, providing new perspectives on one of the leading statesmen of the twentieth century."--